Tingkat Kepuasan Mahasiswa DIV Terapi Gigi Terhadap Kualitas Mengajar Para Dosen di Jurusan Kesehatan Politeknik Kesehatan Kemenkes Makassar - Asriawal; Syamsuddin AB; Baharuddin; Monika Sari (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2024)
This study aims to measure the level of student satisfaction and the quality of academic services at the Health Department of the Health Polytechnic of the Ministry of Health Makassar, covering five dimensions: tangible, reliability, responsiveness, assurance, and empathy. The sample of the study consisted of 58 students. The data were analyzed using descriptive analysis to assess student satisfaction and the quality of teaching provided by lecturers. The results of the study show that (1) students are moderately satisfied with the academic services at the Health Department of the Health Polytechnic of the Ministry of Health Makassar, and (2) the quality of academic services at the Health Department is considered good. The student satisfaction level is divided into five dimensions, with the results indicating that in the tangible dimension, students are moderately satisfied, while in the dimensions of reliability, responsiveness, assurance, and empathy, students are satisfied. Based on the quality of academic services at the Health Department of the Health Polytechnic of the Ministry of Health Makassar, the tangible dimension is categorized as fairly good, the reliability dimension as good, and the responsiveness, assurance, and empathy dimensions as moderately good.